Ligand-modified metal clusters for gas separation and purification - Okrut Alexander; Ouyang Xiaoying; Runnebaum Ron; Gates Bruce C; Katz Alexander (2017)
Provided is an organic ligand-bound metal surface that selects one gaseous species over another. The species can be closely sized molecular species having less than 1 Angstrom difference in kinetic diameter. In one embodiment, the species comprise carbon monoxide and ethylene. Such organic ligand-bound metal surfaces can be successfully used in gas phase separations or purifications, sensing, and in catalysis.